Social Distancing, Stimulus Payments, and Domestic Violence: Evidence from the US during COVID-19 - Bilge Erten; Pinar Keskin; Silvia Prina (Institute of Labor Economics (IZA), 2022)
We examine the effects of social distancing in response to the COVID-19 pandemic on the reporting of domestic violence to the police in the United States. Using daily domestic violence calls from 31 police departments for the January-September 2020 (compared to 2019), we find that the early spike in police calls disappears around mid-April, coinciding with the distribution of CARES Act stimulus payments. We observe that domestic violence calls for areas with higher concentration of Hispanics and noncitizens remain elevated even after this period. These results underscore the importance of improved access to social safety programs in combating domestic violence.
Keywords: J12; J15; I18; 330